Bacteria sense virus-induced genome degradation via methylated mononucleotides - Ilya Osterman; Bohdana Hurieva; Sarit Moses; Alla H. Falkovich; Maxim Itkin; Sergey Malitsky; Eliane Hadas Yardeni; Erez Yirmiya; Rotem Sorek (Science, 2026)
Phages often degrade the genome of their bacterial host to individual nucleotides. Here we describe Metis, a bacterial defense system that directly senses phage-mediated host genome degradation. Metis aborts phage infection once it detects the modified mono-nucleotide m 6 dAMP. As methylation of deoxyadenosines usually occurs on the DNA polymer, accumulation of m 6 dAMP signals that the host genome has been degraded. In type I Metis, sensing of m 6 dAMP activates an NAD + diphosphatase, leading to NAD + depletion and cessation of the infection process; while the effector in type II Metis is a membrane-spanning protein whose toxicity is triggered in response to the modified mono-nucleotide. We further show that Metis defense depends on endogenous DNA methylases, and that phages can escape Metis via mutations that inactivate host genome degradation.